The Slack Channel Deletion Causes Mechanical Pain Hypersensitivity in Mice - Liu, Ye; Zhang, Fang-Fang; Song, Ying; Wang, Ran; Zhang, Qi; Shen, Zhong-Shan; Zhang, Fei-Fei; Zhong, Dan-Ya; Wang, Xiao-Hui; Guo, Qing; Tang, Qiong-Yao; Zhang, Zhe (Frontiers in Molecular Neuroscience, 2022)
The role of the Slack (also known as Slo2.2, KNa1.1, or KCNT1) channel in pain-sensing is still in debate on which kind of pain it regulates. In the present study, we found that the Slack-/- mice exhibited decreased mechanical pain threshold but normal heat and cold pain sensitivity. Subsequently, X-gal staining, in situ hybridization, and immunofluorescence staining revealed high expression of the Slack channel in Isolectin B4 positive (IB4+) neurons in the dorsal root ganglion (DRG) and somatostatin-positive (SOM+) neurons in the spinal cord. Patch-clamp recordings indicated the firing frequency was increased in both small neurons in DRG and spinal SOM+ neurons in the Slack-/- mice whereas no obvious slow afterhyperpolarization was observed in both WT mice and Slack-/- mice. Furthermore, we found Kcnt1 gene expression in spinal SOM+ neurons in Slack-/- mice partially relieved the mechanical pain hypersensitivity of Slack-/- mice and decreased AP firing rates of the spinal SOM+ neurons. Finally, deletion of the Slack channel in spinal SOM+ neurons is sufficient to result in mechanical pain hypersensitivity in mice. In summary, our results suggest the important role of the Slack channel in the regulation of mechanical pain-sensing both in small neurons in DRG and SOM+ neurons in the spinal dorsal horn.